2014
DOI: 10.1186/1749-7221-3-18
|View full text |Cite
|
Sign up to set email alerts
|

Spinal myoclonus following a peripheral nerve injury: a case report

Abstract: Spinal myoclonus is a rare disorder characterized by myoclonic movements in muscles that originate from several segments of the spinal cord and usually associated with laminectomy, spinal cord injury, post-operative, lumbosacral radiculopathy, spinal extradural block, myelopathy due to demyelination, cervical spondylosis and many other diseases. On rare occasions, it can originate from the peripheral nerve lesions and be mistaken for peripheral myoclonus. Careful history taking and electrophysiological evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Spinal myoclonus can be further subclassified into focal spinal myoclonus (FSM), segmental spinal myoclonus (SSM) and proprioceptive spinal myoclonus (PSM) 3. FSM corresponds to myoclonus confined to single spinal myotomes while SSM describes muscle twitches that correspond to several associated spinal myotomes,4 originating from one or few adjacent segments of the spinal cord 5. This is usually due to localised damage to spinal nerves or changes in the function of the underlying spinal cord, with the clinical presentation affecting those body parts correlated to the anatomical location of the lesion.…”
Section: Discussionmentioning
confidence: 99%
“…Spinal myoclonus can be further subclassified into focal spinal myoclonus (FSM), segmental spinal myoclonus (SSM) and proprioceptive spinal myoclonus (PSM) 3. FSM corresponds to myoclonus confined to single spinal myotomes while SSM describes muscle twitches that correspond to several associated spinal myotomes,4 originating from one or few adjacent segments of the spinal cord 5. This is usually due to localised damage to spinal nerves or changes in the function of the underlying spinal cord, with the clinical presentation affecting those body parts correlated to the anatomical location of the lesion.…”
Section: Discussionmentioning
confidence: 99%
“…The ensuing success has been attributed to the interruption of abnormal afferent impulse generation [9]. Savrun et al describe the onset of segmental spinal myoclonus following an ulnar nerve injury [10]. Involuntary movements emerged and intensified over a period of months eventually involving the patient's entire arm.…”
Section: Discussionmentioning
confidence: 99%
“…Involuntary movements emerged and intensified over a period of months eventually involving the patient's entire arm. Electromyography confirmed progression to the C5 and C8 nerve roots [10]. Likewise, Assal et al reported a movement disorder following injury to the cutaneous branch of the deep peroneal nerve with subsequent myoclonus of the first dorsal interosseus muscle [6].…”
Section: Discussionmentioning
confidence: 99%
“…In the systematic review by van Rooijen et al that reviewed 713 patients (from 133 publications), 95 patients (13%) had myoclonus, in isolation or combination with other movement disorders, after peripheral trauma [4]. There are reports of different types of myoclonus (segmental, propriospinal) after accidental and iatrogenic injuries [96][97][98]. Myoclonus may coexist with dystonia and tremor in some patients with CRPS [13].…”
Section: Myoclonus and Polyminimyoclonusmentioning
confidence: 99%